Towards Establishing Zimbabwe Tourism Destination Brand Equity Variables through Sustainable Community Involvement - Chigora, Farai; Mutambara, Emmanuel; Ndlovu, Joram; Muzurura, Joe; Zvavahera, Promise (Africa Journals, 2021)
The study investigated the contribution of local communities to Zimbabwe tourism destination brand equity through sustainable tourism practices, with a view of developing a model. A comparative investigation of two popular resorts in Zimbabwe which are Victoria Falls and Domboshava Curves was carried out. A sequential mixed method was used to get research data. Results from in-depth interviews showed that sustainable brand equity through community involvement can be developed from the following: maintaining culture; attractive traditional villages; traditional music and dances; unique traditional dressing; provision of indigenous food and drinks; guiding tourists and provision of transport and accommodation. A further survey then produced variables that were used to construct a community based sustainable brand equity model for the study. These variables were then grouped into two that is, household activities and service provision. Household activities included: providing indigenous food and drinks; attractive homesteads; and unique dress code. The service provision was discovered as guiding tourists in their activities and provision of transport. The study then recommended local eco-responsibility, destination manager partner with locals, cultural tourism focus and customisation of sustainable tourism.